Pengaruh accounting conservatism, income smoothing dan free cash flow terhadap earning response coefficient pada perusahaan non jasa keuangan yang terdaftar di Bursa Efek Indonesia (BEI) pada tahun 2010 – 2019 - Aritonang , Rosdewita; Ariefianto , Moch. Doddy (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the effect of accounting conservatism, income smoothing, on earnings response coefficient and leverage, growth opportunity as a control variable. This research uses quantitative methods, namely the type of research that obtains data in the form of numbers or data that is numbered. The independent variables in the study are accounting conservatism, income smoothing and free cash flow. The dependent variable in this study is the earning response coefficient, the control variables in this study are leverage and growth opportunity. The data that has been collected will be processed and analyzed using the Stata 14 application. This test is divided into several tests including the descriptive test, the classical assumption test where this test consists of normality, multicollinearity, autocorrelation and heteroscedasticity tests. In addition, a hypothesis test was conducted which consisted of panel data regression test, t test, f test and the coefficient of determination. Accounting conservatism has no effect on the earnings response coefficient in non-financial service companies from 2010-2019, so the results of this panel data regression do not support the initial hypothesis of the study.